PENGARUH KEPUASAN KERJA DAN MODAL PSIKOLOGIS TERHADAP KEINGINAN BERPINDAH MELALUI KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL MEDIASI (Studi Pada Pegawai PT. Bank Mandiri KCP.Bangkong Semarang) - Apriliyana Megawati, 1352020094; Tjahjaningsih, Endang (Jurnal Mahasiswa Pasca Sarjana, 2015)
The purpose of this study was to determine the effect job satisfaction, psychological capital and organizational commitment to Turnover Intention the employees of PT. Bank Mandiri (Persero) Tbk. KCP. Bangkong Semarang at the Credit Colletion& Recovery. The population in this study were employees of PT. Bank Mandiri (Persero) Tbk. KCP. Bangkong Semarang at the Credit Colletion& Recovery.. Models built on the theoretical framework to describe the variables mediating / intervening then to test 5 (five) hipotesis has been developed to use multiple regression analysis with the model intervening (mediating) analysis. Hypothesis testing results show that job satisfaction is a positive and significant effect on organizational commitment, then the capital of psychology also shows significant results and positive impact on organizational commitment, job satisfaction besides significant and indicates a negative value on turnover intentions, but the results different shown different results where psychological capital and organizational commitment not show significant and positive impact to turnover intentions. Keywords: Job Satisfaction, Capital Psychology, Organizational Commitment and Turnover intentions